Understanding the Impact of Equitable Collaborations between Science Institutions and Community-Based Organizations: Improving Science through Community-Led Research. (22nd March 2022) - ,
Abstract: To advance justice, equity, diversity, and inclusion in science, we must first understand and improve the dominant-culture frameworks that impede progress and, second, we must intentionally create more equitable models. The present authors call ourselves the ICBOs and Allies Workgroup (ICBOs stands for independent community-based organizations), and we represent communities historically excluded from the sciences. Together with institutional allies and advisors, we began our research because we wanted our voices to be heard, and we hoped to bring a different perspective to doing science with and not on communities. We created a community framework to guide our research and we led all aspects of our work, from creating research protocols to analyzing and interpreting the data to disseminating the results. We share our research framework, methods, and results so that science institutions can better understand how to intentionally create more equitable research partnerships with our communities.